A high TSH level is associated with diabetic macular edema: a cross-sectional study of patients with type 2 diabetes mellitus. Issue 7 (29th June 2022) - Cao, Xi; Lu, Ming; Xie, Rong-Rong; Song, Li-Ni; Yang, Wei-Li; Xin, Zhong; Yang, Guang-Ran; Yang, Jin-Kui
Abstract : Aims: In this study, we determined the association between thyroid-stimulating hormone (TSH) and diabetic macular edema (DME) by assessing the prevalence and risk factors for DME in type 2 diabetes mellitus (T2DM) patients with different thyroid dysfunctions. Methods: This was a retrospective cross-sectional study including 1003 euthyroid and 92 subclinical hypothyroidism (SCH) T2DM patients. DME status was detected by optical coherence tomography (OCT). The association between TSH and DME and the impact of TSH on DME were analyzed. Results: The DME prevalence was 28.3% in the SCH patients and 14.0% in the euthyroid population. The serum FT4 ( P  = 0.001) and FT3 ( P < 0.001) levels were significantly higher in the non-DME group than in the DME group, and the TSH level ( P < 0.001) was significantly lower. Four subgroups (G1–G4) were divided by TSH level, and the chi-square test indicated that even in the normal range, the TSH level was positively related to DME prevalence ( P  = 0.001). Subgroup data indicated that the association between TSH and DME detected by OCT ( P  = 0.001) was stronger than the correlation between TSH and diabetic retinopathy detected by digital retinal photographs ( P  = 0.027). The logistic regression model confirmed that elevated TSH was an independent risk factor for DME. The odds ratio was 1.53 ( P  = 0.02). Conclusions: A high TSH level was an independent risk factor for DME. More attention should be given to the TSH level in T2DM patients due to its relationship with diabetic complications.